Temperament Predicts Processing Speed in Low Socioeconomic Status Rural Preschoolers - Hermida, María Julia; Segretin, María Soledad; Shalóm, Diego Edgar; López-Rosenfeld, Matías; Abril, Marcelo Claudio; Lipina, Sebastián Javier; Sigman, Mariano (Wiley, 2020)
Extreme poverty all over the world is concentrated in rural settings. However, studies about cognition in low socioeconomic status (SES) children are for the most part conducted in urban populations. This paper investigates, in a poor rural sample, what are the individual and socioenvironmental variables that make the difference in performance in a processing speed task. Forty four 5-year-old children were evaluated with a processing speed task; individual and socioenvironmental information was obtained from parents’ interviews. Higher scores in the effortful control dimension of temperament were associated with higher performance in the processing speed task. No other individual or socioenvironmental variable predicted the performance. These results showed that effortful control is important in processing speed and suggest that in low SES rural contexts, low effortful control children would require stronger interventions
Keywords: Ciencias sociales::Ciencias de la educación